1994
DOI: 10.1007/bf00627754
|View full text |Cite
|
Sign up to set email alerts
|

Forest-to-pasture conversion influences on soil organic carbon dynamics in a tropical deciduous forest

Abstract: On a global basis, nearly 42% of tropical land area is classified as tropical deciduous forest (TDF) (Murphy and Lugo 1986). Currently, this ecosystem has very high deforestation rates; and its conversion to cattle pasture may result in losses of soil organic matter, decreases in soil fertility, and increases in CO flux to the atmosphere. The soil organic matter turnover rate in a TDF after pasture conversion was estimated in Mexico by determining natural abundances ofC. Changes in these values would be induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 34 publications
3
31
0
9
Order By: Relevance
“…The silt and clay fraction had the narrowest C/N ratios, suggesting the most humified state and potentially the largest degree of microbial origin. The increasing degree of humification with decreasing fraction size accords with the results of many previous studies (Elliott, 1986;Oades et al, 1987;Beare et al, 1994;García-Oliva et al, 1994).…”
Section: Land Use and Management-induced Changes Within The Tested Fosupporting
confidence: 92%
“…The silt and clay fraction had the narrowest C/N ratios, suggesting the most humified state and potentially the largest degree of microbial origin. The increasing degree of humification with decreasing fraction size accords with the results of many previous studies (Elliott, 1986;Oades et al, 1987;Beare et al, 1994;García-Oliva et al, 1994).…”
Section: Land Use and Management-induced Changes Within The Tested Fosupporting
confidence: 92%
“…Forest-to-pasture conversion results in 77% and 82% losses of C and N, respectively, from aboveground biomass . As a result of management, soil organic matter decomposes at rates of 2.9 Mg • ha -1 • yr -1 (García-Oliva et al 1994). Soil nutrient loss associated with erosion accelerates several orders of magnitude up to 179 and 24 kg • ha -1 • yr -1 of N and P, respectively (Maass et al 1988), and soil aggregates deteriorate, loosing their stability .…”
Section: The Most Important Servicesmentioning
confidence: 99%
“…The high levels of soil C in young pastures may originate from the original forest. Several authors have reported an increase in soil C directly following forest clearing due to the decomposition of remaining litter and root material [Garcia-Oliva et al, 1994;McAllister et al, 1998]. After several years under pasture, decomposition of soil C and a low input of litter result in decreasing carbon levels, which are lower than the original level at pasture establishment.…”
Section: Landscape Variation In the Response Of Soil C Following Forementioning
confidence: 99%